Comparative Study of Chanoyu Tea and Tea Serving in Yogyakarta Palace - Teti Indriati Kastuti; Christine Dian Permatasari (IZUMI, 2020)
The researcher's experience of studying chanoyu for one year at Urasenke Kyoto became a stimulus to compare Chanoyu tea serving ceremony and tea serving ceremony in Yogyakarta Palace. Up to this time, the tea serving ceremony in Yogyakarta Palace has never been opened to the public, unlike the worldwide Chanoyu tea serving ceremony, a particular school has even been opened to study chanoyu. With this phenomenon, researchers are interested in examining further to compare the two tea serving ceremonies. The method used is descriptive qualitative with literature study, field observation, and interview. The results show that tea used in chanoyu was called powdered matcha, while in Yogyakarta Palace it was 2 Tang powder tea. The utensil in chanoyu is free to choose according to the guests and the season. At the same time, in Yogyakarta palace, it has become the rule and only for families in Yogyakarta Palace. The philosophical meaning of chanoyu is related to the harmony seen in the interaction between participants, as well as between utensil and seasons, while tea serving in Yogyakarta Palace begins with the service of Abdi Dalem to his king. Both of them have similarities in the presentation that must follow the patent rules.